Aquisição da Língua Materna : estudo do processo da avaliação das crianças do primeiro ano do ensino fundamental em comunidades de aprendizagem - Lopes, Ana Lucia Masson (2009)
This dissertation was developed based on the research line Teaching and Learning Processes and aimed to investigate the contribution of the collective-elaboration process of evaluation instruments in Communities of Learning to the first-year elementary school students‟ learning, regarding reading and writing abilities. The utilized Comunicativa Critica methodology, which was developed by the Special Centre of Investigation into Inequality- Surpassing Theories and Practices (CREA) at the University of Barcelona, is based on the Habermas‟ Communicative Action and Freire‟s Concept of Dialogicity. The data were collected during the Curricular Activity of Integration, Teaching, Research and Extension (ACIEPE) Communities of Learning Articulation between school and society in 2008, using evaluative instruments produced in conjunction with teachers and researchers, who had systematic access to the topics of the language to be taught in the first year and to the contents present in official documents on Evaluation, specifically the Provinha Brasil. In the end of the evaluations the reports were turned in and provided the data to be analysed with the participation of the teachers. In respect of the intersubjective analyses, the examined data were related to the first and third evaluations, which allowed their comparison. These intersubjective analyses took place in two different occasions, one collectively and the other with one of the teachers who participated in this process. The results indicated some transforming elements such: the conception of the language and of the describers by the teachers and the importance of a work drawn to the reading and, as obstacles, the limitation of the evaluative instruments regarding their own correction and the partial students‟ involvement. Taking into consideration the whole process of construction and analysis of the data there was a (re)planning of the teacher‟s actions in the classroom. Reflection about the didactic method enabled the students to learn more effectively and promoted pedagogical work reorganization in the Communities of Learning, seeking the improvement of the education quality for all.